Living with the Zeekoevlei: an ethnography on historicizing relationships with/to plastic, wastewater and solid waste pollution - Abrahams, Naailah (Social Anthropology, 2024)
This thesis explores the complexities of plastic and solid waste pollution within and surrounding the Zeekoevlei, located in Cape Town, South Africa. This research focuses on waste pollution being a remnant of an unjust past that still manifests in the present and will seep into the future. The current practices of dealing with waste by the City of Cape Town's waste management and natural resource managers as well as many residents in the city, is to see plastic and other forms of pollution as a 'now' problem, leading to reactive rather than proactive responses. When waste management logics are limited to the 'now', they fail to acknowledge how the current waste crisis in Cape Town is deeply intertwined with unequal settlement histories where indigenous and people of colour were settled in what Lerner (2010) refers to as 'sacrifice zones' and the implications of waste seeping into deep futures. It argues that a paradigm shift in all spheres of society is crucial in changing how we engage, manage, think about, and interact with wastes. The aim of this research is to show that the waste crisis is not new but rather located within histories of injustice, displacement, oppression, inequality, and violence. While a discussion of the futures of waste is also important the objective of this thesis is to trace how these geographies of waste and geographies of violence came to be in the Zeekoevlei. Based on roughly five months of fieldwork in the Zeekoevlei area with The Friends of Zeekoevlei and Rondevlei, what became increasingly significant was the ways in which history had manifested itself in this landscape and how notions of care are emerging in civil societies as a response to the waste crisis. Fieldwork primarily took form through clean- ups of the Zeekoevlei and surrounding areas. Working with FOZR provided a greater sense of the socio-economic issues that are contributing to the waste pollution in the area. Specific research questions include: What relationships and meanings are embedded within plastic and solid wastes? What does this 'say' about our histories with solid wastes? How are people relating to solid wastes in the Zeekoevlei and surrounding landscapes? And what notions of care, kindness and reciprocity are emerging in civil societies? I respond to these questions by drawing from past and current debates in the environmental humanities, urban studies, law, geographical and historical sciences, environmental, cultural, and social anthropology. The evidence basis for this study includes experiences and relationships related by Zeekoevlei residents, archival and anthropological data, contributing to environmental humanities scholarship at the intersection of social and environmental anthropology